Phytochemical Analysis and Anti-Biofilm Potential That Cause Dental Caries from Black Cumin Seeds (Nigella sativa Linn.) - Kurnia D; Padilah R; Apriyanti E; Dharsono HDA (Dove Medical Press, 2024)
Dikdik Kurnia,1 Rizal Padilah,1 Eti Apriyanti,1 Hendra Dian Adhita Dharsono2 1Department of Chemistry, Faculty of Mathematics and Natural Science, Universitas Padjadjaran, Sumedang, Indonesia; 2Department of Conservative Dentistry, Faculty of Dentistry, Universitas Padjadjaran, Bandung, Jawa Barat, IndonesiaCorrespondence: Dikdik Kurnia, Jl. Raya Bandung Sumedang km.21, Hegarmanah, Jatinangor, Kabupaten, Sumedang, Jawa Barat, 45363, Indonesia, Tel/Fax +62 (022) 7794391, Email dikdik.kurnia@unpad.ac.idAbstract: The oral cavity is an excellent place for various microorganisms to grow. Spectrococcus mutans and Spectrococcus sanguinis are Gram-negative bacteria found in the oral cavity as pioneer biofilm formers on the tooth surface that cause caries. Caries treatment has been done with antibiotics and therapeutics, but the resistance level of S. mutans and S. sanguinis bacteria necessitates the exploration of new drug compounds. Black cumin (Nigella sativa Linn.) is known to contain secondary metabolites that have antioxidant, antibacterial, anti-biofilm, anti-inflammatory and antifungal activities. The purpose of this review article is to present data on the potential of Nigella sativa Linn seeds as anti-biofilm. This article will discuss biofilm-forming bacteria, the resistance mechanism of antibiotics, the bioactivity of N. sativa extracts and seed isolates together with the Structure Activity Relationship (SAR) review of N. sativa compound isolates. We collected data from reliable references that will illustrate the potential of N. sativa seeds as anti-biofilm drug.Keywords: Nigella sativa Linn, dental caries, antibiotics, anti-biofilm, S. mutans, S. sanguinis